2018
DOI: 10.1039/c7tb02534c
|View full text |Cite
|
Sign up to set email alerts
|

Internalization studies on zeolite nanoparticles using human cells

Abstract: Internalization of zeolite L is a caveolin-mediated process, which is higher and faster in breast cancer cells than in normal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…All these structures present high thermal and chemical stability and are capable of introducing more than one metal by ion exchange, in order to compensate the negative charge of the framework. 21,22,27,28 Although NaY and NaA show a higher cation-exchange capacity due to their Si/Al ratio (NaY, Si/Al = 2.40, used in this study and 2.83; 22 NaA, Si/Al = 1.24, 41 compared to ZSM-5, Si/Al = 15.0), 42 the location of the cations is dependent on the charge-compensating cations in the structures, which confer the antimicrobial behavior to the samples (Figure 1). 21,22,41−43 Therefore, the preparation of the metal ion−zeolite materials was obtained by two-step insertion of the metal ions in liquid phase: (i) introduction of the first metal ion into the zeolite structure followed by (ii) the insertion of the second metal ion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these structures present high thermal and chemical stability and are capable of introducing more than one metal by ion exchange, in order to compensate the negative charge of the framework. 21,22,27,28 Although NaY and NaA show a higher cation-exchange capacity due to their Si/Al ratio (NaY, Si/Al = 2.40, used in this study and 2.83; 22 NaA, Si/Al = 1.24, 41 compared to ZSM-5, Si/Al = 15.0), 42 the location of the cations is dependent on the charge-compensating cations in the structures, which confer the antimicrobial behavior to the samples (Figure 1). 21,22,41−43 Therefore, the preparation of the metal ion−zeolite materials was obtained by two-step insertion of the metal ions in liquid phase: (i) introduction of the first metal ion into the zeolite structure followed by (ii) the insertion of the second metal ion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The substitution of Al 3+ for Si 4+ in TO 4 induces a negative charge in the zeolite structure, which is balanced by the exchangeable cation to preserve the electroneutrality of the solid, resulting in a higher cation-exchange capacity. Zeolites can be natural or synthetic, the latter having more advantages than the natural ones due to higher purity, a more uniform pore size, and better ion-exchange abilities. , All these properties make zeolites suitable for different applications in catalysis, drug delivery systems, adsorption, ion exchange, and separation. These structures have also been used as antimicrobial agents upon introduction of metal ions with antimicrobial properties by the ion-exchange method, namely, silver, ,,,,, zinc, ,, and copper. ,,, .…”
Section: Introductionmentioning
confidence: 99%
“…Free Cy5 and Cy5 loaded NPs without membrane coating (Cy5-N) and Cy5 loaded membrane coated NPs (Cy5-MN) (each containing the same content of Cy5) were added into the medium of BMDM and Caco-2 cells with the final concentration of Cy5 as 10 μg/mL and the concentration of NPs as 0.19 mg/mL. The internalization of free Cy5 and Cy5 loaded NPs was determined by flow cytometry in 4 hours and 24 hours, respectively according to the previous studies 30 , 31 and the mean fluorescence intensity was statistically analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…43 The current results are also in an agreement with other studies reported that nanoparticles with a size of 50 nm and 120 nm are internalized faster in comparison to 250 nm particles. 44 In a very recent study, 45 the kinetics of uptake of zeolite L and NaY by Hs 578T breast cancer cells and MCF-10 epithelial mammary cells was presented. The NaY zeolite had cubic geometry with an average diameter of 700 nm, while zeolite L had disc-shaped particles with a size of around 400 nm.…”
Section: Nanosized Ru(bpy)3-fau Zeolite As An Intracellular Localization Tracermentioning
confidence: 99%